2002
DOI: 10.1007/s00455-001-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Swallow-Induced Alterations in Breathing in Normal Older People

Abstract: Respiratory parameters in 29 normal older subjects (mean age-73 years, SD = 5.7) were studied at rest, during single water swallows, and in continuous drinking. Respiration was recorded by intranasal air pressure changes and the moment of swallowing by pharyngoesophageal manometry. Compared with respiration at rest, respiratory rate increased immediately after 5 mL swallows as duration of breath cycles decreased from a mean of 3.8 s at rest to 3.5 s after swallowing (p = 0.003), but regularity of respiration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 25 publications
9
62
0
4
Order By: Relevance
“…Earlier SA onset likely contributes to the increased SA duration with increased bolus SA ONSET 14 volumes reported in previous research. It should be noted that while some research has reported that SA duration increased as a function of bolus volume (Issa & Porostocky, 1994;Preiksaitis & Mills, 1996;Hiss et al, 2001;Hirst, Ford, Gibson, & Wilson, 2002), other research has reported that SA duration was not influenced by bolus volume (Preiksaitis, Mayrand, Robbins, & Diamant, 1992;Martin, Logemann, Shaker, & Dodds, 1994). The most recent studies investigating SA duration that have employed a larger number of participants, advanced technology, and normal eating/drinking simulation coupled with the findings of the current study (i.e., onset of SA started earlier with increases in bolus volume) provide strong evidence that SA duration does increase with increases in bolus volume.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier SA onset likely contributes to the increased SA duration with increased bolus SA ONSET 14 volumes reported in previous research. It should be noted that while some research has reported that SA duration increased as a function of bolus volume (Issa & Porostocky, 1994;Preiksaitis & Mills, 1996;Hiss et al, 2001;Hirst, Ford, Gibson, & Wilson, 2002), other research has reported that SA duration was not influenced by bolus volume (Preiksaitis, Mayrand, Robbins, & Diamant, 1992;Martin, Logemann, Shaker, & Dodds, 1994). The most recent studies investigating SA duration that have employed a larger number of participants, advanced technology, and normal eating/drinking simulation coupled with the findings of the current study (i.e., onset of SA started earlier with increases in bolus volume) provide strong evidence that SA duration does increase with increases in bolus volume.…”
Section: Discussionmentioning
confidence: 96%
“…Examples include surface electromyography or other physiological tracings (4,5,9,17,21,25,26,31,34). Although the indirect measures of swallowing are generally less invasive and permit the acquisition of greater numbers of swallowing samples, their clinical utility is suspect without simultaneous direct visual confirmation of the swallowing mechanics occurring with respiratory activity.…”
mentioning
confidence: 99%
“…This approach allows calculating average droplet velocities between several positions along the vertical droplet trajectory according to eq. (2): (2) where ∆y is the distance covered by the drop between two light barriers and ∆t the time of flight between those positions. Figure 4 shows the measurement setup with the highlighted measuring section ∆y = 100 mm.…”
Section: Measurement Setupmentioning
confidence: 99%
“…Correspondingly, pneumonia is among the top ten causes of death in the elderly in the United States (age > 65) [1]. In healthy individuals, several mechanisms prevent irruption of particles into the subglottic space, the trachea and deeper airways [2]. One key mechanism is the fast, reflexive closing of the vocal folds following appropriate stimulation of the glottal mucosa, known as the Laryngeal Adductor Reflex (LAR).…”
Section: Introductionmentioning
confidence: 99%